The Bending–Gradient theory for the linear buckling of thick plates: Application to Cross Laminated Timber panels. (1st June 2016) - Perret, Olivier; Lebée, Arthur; Douthe, Cyril; Sab, Karam
Abstract: In this paper, the linear buckling of a heterogeneous thick plate is studied using the Bending–Gradient theory which is an extension of the Reissner–Mindlin plate theory to the case of heterogeneous plates. Reference results are taken from a 3D numerical analysis using finite-elements and applied to Cross Laminated Timber panels which are thick and highly anisotropic laminates. First, it is shown that critical buckling loads are close to the material failure load which proves the necessity of a design model for the buckling of Cross Laminated Timber panels. Second, the soft simple support boundary condition is introduced as an opposition to the conventional hard simple support condition. It is shown that this distinction could be taken into account for designing timber structures depending on the accuracy needed. Third, it is observed that for varying plate geometries and arrangements, the Bending–Gradient theory predicts more precisely the critical load of CLT panels than classical lamination and first-order shear deformation theories. Finally, it is demonstrated that one of the suggested projections of the Bending–Gradient on a Reissner–Mindlin model gives very accurate results and could favorably allow the development of engineering recommendations for estimating properly transverse shear effects.